Let Others Buy First: Identity Fusion Buffers the Effect of COVID-19 Phobia on Panic Buying Behavior From an Economic Perspective - Seih, Yi-Tai; Tra, Vi Thanh; Lepicovsky, Marketa; Chang, Yi-Ying (Frontiers in Psychology, 2021)
The coronavirus 2019 (COVID-19) pandemic has caused hundreds of millions of cases and millions of deaths, resulting in the development of COVID-19 phobia. To prevent getting COVID-19, Centers for Disease Control and Prevention (CDC) in many countries encourage people to protect themselves via several strategies, such as wearing face masks or using sanitizers when washing hands. However, at times, such supplies for preventing COVID-19 are limited. In this study, we examine the relationship between COVID-19 phobia and panic buying behavior from an economic perspective and test if identity fusion plays a buffering role for this phenomenon. Data was collected from September 4th to November 1st in 2020 across three countries (the United States, Germany, and Taiwan). A self-report measure of panic buying behavior was developed and culturally cross-validated. Moderation analyses were conducted focusing on the study objectives. Results show that the economic factor in COVID-19 phobia predicts panic buying behavior, and this effect is buffered by identity fusion. It is worthy to note that this buffering effect emerged only in the Taiwanese sample, not in the American or German samples. Implications of identity fusion theory in human behavior are discussed.